Influence of Host Sialic Acid Receptors Structure on the Host Specificity of Influenza Viruses - Chuankuo Zhao; Juan Pu (Viruses, 2022)
Influenza viruses need to use sialic acid receptors to invade host cells, and the α-2,3 and α-2,6 sialic acids glycosidic bonds linking the terminal sialic acids are generally considered to be the most important factors influencing the cross-species transmission of the influenza viruses. The development of methods to detect the binding of influenza virus HA proteins to sialic acid receptors, as well as the development of glycobiological techniques, has led to a richer understanding of the structure of the sialylated glycan in influenza virus hosts. It was found that, in addition to the sialic acid glycosidic bond, sialic acid variants, length of the sialylated glycan, Gal-GlcNAc-linked glycosidic bond within the sialylated glycan, and sulfation/fucosylation of the GlcNAc within the sialylated glycan all affect the binding properties of influenza viruses to the sialic acid receptors, thus indirectly affecting the host specificity of influenza viruses. This paper will review the sialic acid variants, internal structural differences of sialylated glycan molecules that affect the host specificity of influenza viruses, and distribution characteristics of sialic acid receptors in influenza virus hosts, in order to provide a more reliable theoretical basis for the in-depth investigation of cross-species transmission of influenza viruses and the development of new antiviral drugs.